Intravenous dexmedetomidine versus clonidine for prolongation of bupivacaine spinal anesthesia and analgesia: A randomized double-blind study - Velayudha Sidda Reddy; Nawaz Ahmed Shaik; Balaji Donthu; Venkata Krishna Reddy Sannala; Venkatsiva Jangam (Wolters Kluwer Medknow Publications, 2013)
Background: Alpha 2 -adrenergic agonists have synergistic action with local anesthetics and may prolong the duration of sensory, motor blockade and postoperative analgesia obtained with spinal anesthesia. Aim: The objectives of this study are to compare and evaluate the efficacy of intravenous dexmedetomidine premedication with clonidine and placebo on spinal blockade duration, postoperative analgesia and sedation in patients undergoing surgery under bupivacaine intrathecal block. Materials and Methods: In this prospective, randomized, double-blind placebo-controlled study, 75 patients of the American Society of Anesthesiologists status I or II, scheduled for orthopedic lower limb surgery under spinal anesthesia, were randomly allocated into three groups of 25 each. Group DE received dexmedetomidine 0.5 μgkg−1 , group CL received clonidine 1.0 μgkg−1 and placebo group PL received 10 ml of normal saline intravenously before subarachnoid anesthesia with 15 mg of 0.5% hyperbaric bupivacaine. Onset time and regression times of sensory and motor blockade, the maximum upper level of sensory blockade were recorded. Duration of postoperative analgesia and sedation scores along with side effects were also recorded. Data was analyzed using analysis of variance or Chi-square test, and the value of P < 0.05 was considered statistically significant. Results: The sensory block level was higher with dexmedetomidine (T4 ± 1) than clonidine (T6 ± 1) or placebo (T6 ± 2). Dexmedetomidine also increased the time (243.35 ± 56.82 min) to first postoperative analgesic request compared with clonidine (190.93 ± 42.38 min, P < 0.0001) and placebo (140.75 ± 28.52 min, P < 0.0001). The maximum Ramsay sedation score was greater in the dexmedetomidine group than other two groups (P < 0.0001). Conclusion: Premedication with intravenous dexmedetomidine is better than intravenous clonidine to provide intraoperative sedation and postoperative analgesia during bupivacaine spinal anesthesia.